MicroRNA mediators of early life stress vulnerability to depression and suicidal behavior - Allen, Lauren (Mol Psychiatry, 2019)
Childhood environment can have a profound impact on brain structure and function. Epigenetic mechanisms have been shown to play a critical role in adaptive and maladaptive processes by regulating gene expression without changing the genome. Over the past few years, early life stress (ELS) has been established as a major risk factor for major depression and suicidal behavior along with other psychiatric illnesses in adulthood. In recent years, the emergence of small noncoding RNAs as a mega controller of gene expression has gained attention for their role in various disease processes. Among various noncoding RNAs, microRNAs (miRNAs) are the most studied and well characterized and have emerged as a major regulator of neural plasticity and higher brain functioning. More recently, although limited in number, studies are focusing on how miRNAs can play a role in the maladaptive processes associated with ELS both at adolescent and adult age and whether these processes are critical in developing depression and suicidal behavior. In this review, we critically evaluate how postnatal ELS relates to abnormalities in miRNA expression and functions from both animal and human literature and draw connections from these findings to depression and suicidal behavior later in life.